In-Cell NMR of Intact Mammalian Cells Preserved with the Cryoprotectants DMSO and Glycerol Have Similar DNP Performance - Xiao, Yiling; Ghosh, Rupam; Frederick, Kendra K. (Frontiers in Molecular Biosciences, 2022)
NMR has the resolution and specificity to determine atomic-level protein structures of isotopically-labeled proteins in complex environments and, with the sensitivity gains conferred by dynamic nuclear polarization (DNP), NMR has the sensitivity to detect proteins at their endogenous concentrations. Prior work established that DNP MAS NMR is compatible with cellular viability. However, in that work, 15% glycerol, rather than the more commonly used 10% DMSO, was used as the cellular cryoprotectant. Moreover, incubation of cells cryoprotected 15% glycerol with the polarization agent, AMUPol, resulted in an inhomogeneous distribution of AMUPol, through the cellular biomass, which resulted in a spatial bias of the NMR peak intensities. Because 10% DMSO is not only the most used cryoprotectant for mammalian cells, but also because DMSO is often used to improve delivery of molecules to cells, we sought to characterize the DNP performance of cells that were incubated with AMUPol and cryoprotected with 10% DMSO. We found that, like cells preserved with 15% glycerol, cells preserved with 10% DMSO retain high viability during DNP MAS NMR experiments. However, DMSO did not improve the dispersion of AMUPol throughout the cellular biomass. Cells preserved with 15% glycerol and with 10% DMSO had similar DNP performance for both the maximal DNP enhancements as well as the inhomogeneous dispersion of AMUPol throughout the cellular biomass. Therefore, 10% DMSO and 15% glycerol are both appropriate cryoprotectant systems for DNP-assisted MAS NMR of intact viable mammalian cells.